Nilai-nilai Pendidikan Islam yang terdapat dalam Surat al Maidah ayat 20-26 - Sutarto, Sutarto (JOEAI (Journal of Education and Instruction), 2022)
This study examines Islamic education's values contained in the Qur'an Surah al Maidah verses 20-26. This research is a research library research. Data sources were obtained from the Koran, hadith, commentary books, research results, and scientific journal articles, then analyzed using inductive, deductive, and comparative approaches. The study results show that the values of Islamic education contained in Surah Al Maidah verses 20-26 are related to learning materials. Namely, Allah SWT has given many blessings to His servants. Therefore they must be grateful. In addition, the verse implies that the teacher motivates and prepares everything before carrying out the learning process. In addition, the verse explains that in carrying out learning, it is sometimes found that students are disobedient and do not want to try but want maximum results. Facing students like this, the teacher must speak calmly and gently, not loudly, which can arouse anger. Keywords: Islamic education values, surah al Maidah verses 20-26, characteristics of students